Study on strength and fracture toughness of Al-Zn-Mg-Cu-Ti(-Sn) alloys - Yan A.; Chen L.; Liu H.S.; Xiao F.F.; Li X.Q. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The strength and fracture toughness of Al-Zn-Mg-Cu-Ti(-Sn) alloys were investigated by performing tensile and plane strain fracture toughness (KIC) tests. Detailed observations with optical, scanning electron and transmission electron microscopy were conducted to analyze microstructure and fracture surfaces of the alloys. The results revealed that addition of Sn refined the solution-aging grain size of matrix and reduced coarsening rate of precipitate during aging. Narrower precipitation free zones and more discontinuous distribution of grain boundary precipitates were observed to be displayed in the Sn-containing alloy. Small size second phase particles Mg2Sn were observed to form in the Sn-containing alloy and distribute in the fine dimples of fracture surface. These features of microstructure were believed to impart higher strength and fracture toughness of the Sn-containing alloy on overaging.